2009
DOI: 10.1097/ico.0b013e3181930c03
|View full text |Cite
|
Sign up to set email alerts
|

Staining Patterns in Dry Eye Syndrome: Rose Bengal Versus Lissamine Green

Abstract: Both LG and RB showed similar staining patterns. RB was found to provide greater patient discomfort. There was no correlation between disease severity (addressed by the ocular surface disease index questionnaire) and staining patterns (measured by the van Bijsterveld scale).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 22 publications
0
37
0
1
Order By: Relevance
“…In recent years it has replaced rose bengal in clinical use and for practical purposes, and notwithstanding some small differences in its behaviour at cellular level, lissamine green may be assumed to offer the same opportunities and interpretations as staining with rose bengal (Norn, 1972(Norn, , 1973Emran and Sommer, 1979;Amaki et al, 1999;Kusin et al, 1979;Khurana et al, 1991;Manning et al, 1995;Korb et al, 2008;Bron et al, 2003;Hughes et al, 2003;Doughty et al, 2004;Berntsen et al, 2006;Machado et al, 2009;Yoon et al, 2011). It is well tolerated after instillation and shows less intrinsic toxicity than rose bengal (Chodosh et al, 1994).…”
Section: Lissamine Greenmentioning
confidence: 95%
“…In recent years it has replaced rose bengal in clinical use and for practical purposes, and notwithstanding some small differences in its behaviour at cellular level, lissamine green may be assumed to offer the same opportunities and interpretations as staining with rose bengal (Norn, 1972(Norn, , 1973Emran and Sommer, 1979;Amaki et al, 1999;Kusin et al, 1979;Khurana et al, 1991;Manning et al, 1995;Korb et al, 2008;Bron et al, 2003;Hughes et al, 2003;Doughty et al, 2004;Berntsen et al, 2006;Machado et al, 2009;Yoon et al, 2011). It is well tolerated after instillation and shows less intrinsic toxicity than rose bengal (Chodosh et al, 1994).…”
Section: Lissamine Greenmentioning
confidence: 95%
“…Replicating the test two to three times per eye will provide a more reliable result to determine whether the patient has a rapid TBUT (<10 s) [6,19]. Application of vital stains, including lissamine green and/or rose bengal, allows for a similar level of observation of the integrity of the conjunctiva and cornea [20,21]. The ‘Diagnostics and clinical assessments’ section presents additional detailed information pertaining to the description and interpretation of the diagnostic tests described previously.…”
Section: Diagnosis-based Individualized Treatment Approachmentioning
confidence: 99%
“…6), are recommended to be applied to the ocular surface once the fluorescein evaluation is complete. Vital stains assist in the visualization of debris in the tear film and areas of the ocular surface that do not have a mucus coating (i.e., cells that are ‘unhealthy or abnormal’) [20,21,56]. Table 8 presents corneal/conjunctival lissamine green/rose bengal staining patterns characteristically associated with a range of ocular conditions.…”
Section: Diagnostics and Clinical Assessmentsmentioning
confidence: 99%
“…Sorafenib is the most frequently used drug for liver cancer, however, Sorafenib just can extent 3 months of survival. Rose Bengal is a water-soluble xanthene dye that had been previously used in liver function studies and is still in use by ophthalmologists [Machado et al, 2009]. Several in-vitro studies showed the direct cytotoxicity of rose bengal in ovarian and sarcoma cancer cells [Koevary, 2012].…”
Section: Introductionmentioning
confidence: 99%